Complex Electrical Stimulation Systems in Motor Function Rehabilitation after Spinal Cord Injury - Jiange Kou; Maolin Cai; Fei Xie; Yixuan Wang; Na Wang; Meng Xu (Complexity)
Spinal cord injury (SCI) is an existing incurable disease that brings great pain and life obstacles to patients. Spinal cord electrical stimulation is an effective means to alleviate spinal cord injury. However, its complicated mechanism of action is still unclear. This article aims to summarize several different spinal cord electrical stimulation methods, analyze the stimulation effect, and briefly describe the current understanding of its origin and mechanism of action. In recent years, several application cases of the electrical stimulation system of stimulation methods have confirmed its positive effects in spinal cord injury diseases and provided new perspectives for the improvement of spinal cord injury. Finally, the possible development direction and corresponding challenges of spinal cord electrical stimulation in the future are proposed.